Probing the neutrino mass ordering with KM3NeT-ORCA: analysis and perspectives. (9th January 2018) - Capozzi, Francesco; Lisi, Eligio; Marrone, Antonio
Abstract: The discrimination of the two possible options for the neutrino mass ordering (normal or inverted) is a major goal for current and future neutrino oscillation experiments. Such a goal might be reached by observing high-statistics energy-angle spectra of events induced by atmospheric neutrinos and antineutrinos propagating in the Earth matter. Large volume water-Cherenkov detectors envisaged to this purpose include the so-called KM3NeT-ORCA project (in seawater) and the IceCube-PINGU project (in ice). Building upon a previous work focused on PINGU, we study in detail the effects of various systematic uncertainties on the ORCA sensitivity to the mass ordering, for the reference configuration with 9 m vertical spacing. We point out the need to control spectral shape uncertainties at the percent level, the effects of better priors on the θ 23 mixing parameter, and the benefits of an improved flavor identification in reconstructed ORCA events.